2019
DOI: 10.3390/molecules24234354
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Bark-Extract-Mediated Green Synthesis of Metallic Nanoparticles and Their Applications

Abstract: Nanoparticles are intensely studied because of their importance in diverse fields of biotechnology, especially in medicine. This paper highlights that waste bark can be a cheap source of biocompounds, with high recovery and functionalization potential in nanoparticle synthesis. Due to their biocompatibility and activity as antioxidant, antimicrobial, and anticancer agents, the green synthesis of metallic nanoparticles is of great importance. This review aims to bring together the diversity of synthesized metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 93 publications
0
36
0
3
Order By: Relevance
“…These results indicate that the polyphenols and proteins in the catkin extract have acted as reducing, capping and stabilizing agents, for the nanoparticles, as predicted by the FTIR peaks. They might also have acted as agents for elevated antimicrobial activity as compared to the nanoparticles synthesized by chemical means [48] , [49] , [50] , [51] , [52] , [53] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the polyphenols and proteins in the catkin extract have acted as reducing, capping and stabilizing agents, for the nanoparticles, as predicted by the FTIR peaks. They might also have acted as agents for elevated antimicrobial activity as compared to the nanoparticles synthesized by chemical means [48] , [49] , [50] , [51] , [52] , [53] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Currently, several studies have been reported to produce plant-based eco-friendly repellents possessing larvicidal activity [ 21 , 22 ]. These medicinal plants are used for the synthesis of silver, gold, platinum, copper, and titanium nanoparticles having potent antimicrobial, antioxidant, and anticancer properties [ 23 , 24 ]. These medicinal plants naturally possess bio-surfactant molecules, also called secondary metabolites, such as flavonoids, alkaloids, tannins, saponins, glycosides, and phenols.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomedicine is a promising area that can induce changes affecting cancer treatment protocols, and the green synthesized AgNPs are effective anticancer mediators used for detection, prevention and bioremediation of tumour cells. AgNPs are intimately investigated for their promising anticancer property exhibited against different human cancer cell lines, like IMR-90, MCF-7, U251, MDA-MB-231, HT-29, HeLa, A-549 and HepG2 tumour cells (Burdusel et al, 2018;Burlacu et al, 2019;Nayaka et al, 2020;Rajoka et al, 2020).…”
Section: O N L I N E C O P ÿmentioning
confidence: 99%